2003
DOI: 10.1017/s0031182003003032
|View full text |Cite
|
Sign up to set email alerts
|

Cryptosporidium parvum: infectivity and pathogenicity of the ‘porcine’ genotype

Abstract: Genetic studies have demonstrated profound differences between the 'porcine' genotype of Cryptosporidium parvum, versus 'human' and 'bovine' genotypes. The study analysed infectivity and pathogenicity of the 'porcine' genotype (CPP-13 isolate) of C. parvum, and compared the results with published data on the 'bovine' genotype (CPB-0 isolate). This was investigated in calves and piglets from commercial herds. Piglets were mildly affected by the CPP-13 isolate, contrary to piglets infected with the CPB-0 isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
44
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 26 publications
(37 reference statements)
2
44
0
2
Order By: Relevance
“…Cryptosporidium spp. was diagnosed in only one litter of very young piglets (1-2 days old), agreeing with previous results showing that the beginning of fecal oocysts excretion of this agent varies from 2 to 9 days after infection (Enemark et al 2003).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Cryptosporidium spp. was diagnosed in only one litter of very young piglets (1-2 days old), agreeing with previous results showing that the beginning of fecal oocysts excretion of this agent varies from 2 to 9 days after infection (Enemark et al 2003).…”
Section: Discussionsupporting
confidence: 92%
“…It has been previously demonstrated that there is no relationship between the occurrence of diarrhea and the detection of oocysts of Cryptosporidium in feces, especially in piglets with low levels of infection (Enemark et al 2003). The possible explanation is that diarrhea is caused by pathogens other than Cryptosporidium sp.…”
Section: Discussionmentioning
confidence: 99%
“…In humans and cattle, unformed stools in Cryptosporidium infection reportedly contained as many as 10 5 to 10 6 oocysts per gram of stools 28,29 . Experimental Cryptosporidium infection can cause serious diarrhea, loss of appetite and vomiting in suckling pigs 4 . Diarrhea caused by C. suis in outdoorgrown suckling pigs has also been reported 21 , suggesting C. suis infection as a potential cause of diarrhea in the five pigs in our study that produced partly unformed or unformed stools with oocysts per gram of stools of 10 4 to 10 5 .…”
Section: Discussionmentioning
confidence: 99%
“…Diarrhea caused in pigs by Cryptosporidium allows increased superinfection with other pathogens such as rotavirus (Rota V), porcine circovirus type 2, porcine reproductive and respiratory syndrome virus, and Escherichia coli 4,13,26 . Rota V infection facilitates the growth of Cryptosporidium in the digestive tract of the pig and increases mortality rates 4 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation